The Immunomodulatory Activity of Punica granatum L. Peel Extract Increases the Lifespan of Mice with Lethal Sepsis - Liana de O. Trovão; Liliane dos S. Rodrigues; Priscila M. Mendes; Patrícia C. S. Alves; Aluísio da S. Oliveira; Jefferson M. Brito; André A. M. Vale; Dimitrius V. de O. Garbis; Gisele Simão; Ana Paula S. A. dos Santos; Paulo V. S. Pereira; Lucilene A. Silva; et al. (Journal of Immunology Research)
Sepsis is an organ dysfunction syndrome associated with high mortality. To date, no effective treatment is available to combat this disease. Punica granatum L. is a potential alternative treatment due to its anti-inflammatory, antimicrobial, and antioxidant properties. Thus, this study aimed to evaluate the effects of a hydroalcoholic crude extract from the peels of P. granatum (HCEPg) in mice with lethal sepsis. Lethal polymicrobial sepsis was induced in female Swiss mice via cecal ligation and puncture (CLP). Initially, the animals were divided into three groups: Sham (false-operated), CLP-control (phosphate-buffered saline), and CLP-HCEPg (single dose, 5 mg/kg, subcutaneous administration). Treatment was initiated immediately after the induction of sepsis, and survival was evaluated every 12 hr for 5 days. Those who survived were euthanized. Serum cytokine levels were measured using a cytometric bead array Mouse Inflammatory Cytokine Kit. The number of colony-forming units, as well as the number of cells in the lymphoid organs and their activation markers, were analyzed. Results showed that treatment with HCEPg increased lifespan and reduced bacterial counts in the peritoneum, bloodstream, and spleen. HCEPg also decreased hydrogen peroxide secretion by phagocytes and augmented serum IL-10 levels, indicating its systemic anti-inflammatory effects. Additionally, treatment with HCEPg attenuated infection-induced lung hemorrhage. Overall, P. granatum extract improved the lifespan of septic mice, possibly due to its antimicrobial, anti-inflammatory, and immunomodulatory effects, thereby regulating bacterial load and translocation, as well as controlling the systemic inflammation induced by sepsis.